Lajishankou Ophiolite Complex: Implications for Paleozoic Multiple Accretionary and Collisional Events in the South Qilian Belt. Issue 5 (10th May 2018) - Fu, Changlei; Yan, Zhen; Wang, Zongqi; Buckman, Solomon; Aitchison, Jonathan C.; Niu, Manlan; Cao, Bo; Guo, Xianqing; Li, Xiucai; Li, Yunshuai; Li, Jiliang
Abstract: The Lajishan ophiolite complex in the Qilian Orogen is one of several ophiolites situated between the Qaidam and North China blocks that record episodic closure of the Proto‐Tethyan Ocean. Detailed field relations and geochemical and geochronological studies are critical to unraveling the tectonic processes responsible for an extensive period of intraoceanic subduction that produced juvenile ophiolite/island arc terranes, which were obducted onto continental margins during ocean closure. The Lajishankou ophiolite complex crops out along the northern margin of the South Qilian belt and was thrust over a Neoproterozoic‐Ordovician passive margin sequence that was deposited upon the Proterozoic Central Qilian block. The mafic rocks in Lajishankou ophiolite complex are the most abundant slices and can be categorized into three distinct groups based on petrological, geochemical, and geochronological characteristics: massive island arc tholeiites, 509‐Ma back‐arc dolerite dykes, and 491‐Ma pillow basaltic and dolerite slices that are of seamount origin in a back‐arc basin. These results, together with spatial relationships, indicate that the Cambrian island arc rocks, ophiolite complex, and accretionary complex developed between 530 and 480 Ma as a single, intraoceanic arc‐basin system as a result of south directed subduction of the Proto‐Tethyan Ocean prior to Early Ordovician obduction of this system onto the Central Qilian block. Final continental amalgamation involved continental collision of the Central Qilian block with the Qaidam block during the Late Ordovician. This model solves the long‐lasting discussion on the emplacement of the Lajishan ophiolite and contributes to an improved understanding of multiple accretionary and collisional processes in the Qilian Orogen. Key Points: The Lajishankou ophiolite complex consists of serpentinite, wehrlite, pyroxenite, gabbro, dolerite, pillow, and massive basalts The mafic rocks are geochemically similar to intraoceanic arc‐basin remnants formed during southward subduction of the Proto‐Tethyan Ocean Lajishan ophiolite‐arc rocks were emplaced onto the Central Qilian block during arc‐continent collision